International migration desires related to subjective well-being - Ruohong Cai; Neli Esipova; Michael Oppenheimer; Shuaizhang Feng (IZA Journal of Migration, 2014)
Previous research on the determinants of international migration has largely focused on objective factors, such as income. We instead use subjective well-being (SWB) to explain international migration desires, an expressed willingness to migrate. We find that individuals with higher SWB have lower international migration desires. At the individual level, the SWB-migration relationship appears to be more robust than the income-migration relationship. At the country level, national average SWB better indicates international migration desires for rich countries, while income performs better for poor countries. We thus demonstrate the feasibility of employing subjective measures to study at least one aspect of an important social outcome, migration.
Keywords: F22; O15; I31; 330; Subjective well-being; International migration desires; Income; Logistic regression